Recurrence of left ventricular pseudoaneurysm after multiple mitral valve replacements - Alsomali, Afrah; Eltayeb, Abdullah; Aldosari, Sarah; AlShahid, Maie; AlSanei, Aly; AlEnazy, Ali; Vriz, Olga (Monaldi archives for chest disease, 2021)
Left ventricular pseudoaneurysm (LVPA) formation is a potentially lethal complication of myocardial infarction (MI] and mitral valve (MV) replacement that requires prompt diagnosis and treatment. A female patient who had been complaining of exertional dyspnea underwent a two-dimensional transthoracic echocardiogram (TTE) which revealed a functioning mechanical MV with severe paravalvular leak, severe tricuspid regurgitation (TR) and severely elevated pulmonary artery systolic pressure. Moreover, echo-lucent space at the postero-lateral portion of the left ventricle near the MV was seen, suggestive of a large LVPA. Transesophageal echocardiography (TEE) and Computed Tomography (CT) angiography confirmed these findings. Afterwards, the patient had a surgical repair for the LVPA along with mitral and tricuspid valve (TV) replacement. Three months later, the patient presented with symptoms of congestive heart failure. The LVPA had recurred at the same location of the previous pseudoaneurysm and given the high risk for reoperating on the patient, close monitoring and medical management was deemed as a better option.